GUIDELINES FOR ACADEMIC ADMINISTRATION OF PRIVATE SCHOOLS AFFILIATED WITH MAHA SARAKHAM PROVINCIAL EDUCATION OFFICE USING THE PROFESSIONAL LEARNING COMMUNITY APPROACH - Junsom, Apiwut; Srisa – ard, Boonchom (Journal of MCU Nakhondhat, 2020)
The objectives of this research were 1) to study the current state, desired state, and needs in academic administration of private schools affiliated with Maha Sarakham Provincial Education Office using the professional learning community approach and 2) to study guidelines for academic administration of private schools affiliated with Maha Sarakham Provincial Education Office. The samples included 265 administrators and teachers. It also comprised the open – ended questions. The questionnaire was tried out with other 30 administrators and teachers who were not included as samples in this study in order to verify the quality of questionnaire, revealing that its discrimination index ranged from .67 – .85 and its reliability was .94. The statistics, which were used to consisted of mean, standard deviation, and Priority Needs Index. In terms of guidelines data from schools with the best practice was analyzed. Findings indicated that: the current state of academic administration in overall and in each aspect was at the high level, while the desired state was at the highest level. It was recommended that in the aspect of school curriculum development, administrators and teachers should collaboratively formulate a plan by building PLC for developing a school curriculum based on visions, missions and goals of a school. In the aspect of learning process development, teachers should develop themselves on the techniques for effective and student – centered learning management. In the aspect of measurement, evaluation and transferal of learning outcome, a meeting between administrators and teachers should be organized by building PLC in order to determine regulations or ways of practice about the measurement and evaluation by the school. In the aspect of research for educational quality development and the teachers should be promoted to conduct at least one classroom research project per a learning area in a semester. Moreover, the results of classroom research should be utilized for improving the learning management together with inviting experts to give advices to individual teachers. Lastly, in the aspect of educational supervision, a brainstorming activity based on PLC approach should be conducted to improve the internal supervision.